ANALISIS KESALAHAAN EJAAN TERHADAP TEKS BERITA “BIKIN GAGAL GINJAL, ETILEN GLIKOL DI OBAT SIRUP TERNYATA ‘FAMILIAR’ DI MESIN” PADA MEDIA ONLINE DETIKOTO” - Reva Yulianizar; Siti Zulfa Waliah (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2022)
In online media, writing errors regarding language are often found. One of them is online media in the process of writing news texts sometimes in a hurry because it is based on a predetermined deadline. This error occurs because it violates two of the three terms of word selection, namely "true" and "right". This study aims to (1) describe the form of language errors in terms of the use of word choice and italics contained in the DetikOto online news text, (2) explain the form of errors and language corrections in terms of the use of word choice and italics that dominantly appear in news texts. online detikOto. This research uses a descriptive method. The data of this research are in the form of errors in words and sentences containing language errors in the DetikOto news text. Data collection techniques used are reading, marking errors, identifying, analyzing, and concluding. While the instrument in this study is the researcher himself and the instructions for errors and improvements. Furthermore, the note-taking technique is used to write down the problems in the reading. The note-taking technique used is to record words or sentences which are a form of language error in the field of spelling. After being analyzed and described based on the form of language errors in the field of spelling, errors in spelling in the news text include: 1. Word Choice Errors, 2. Acronym Errors, 3. Title Writing, 4. Italicized Writing. Then concluded from the improvement of the sentence.